2012
DOI: 10.2310/jim.0b013e31823e9d86
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Neutrophil Gelatinase–Associated Lipocalin in ST-Segment Elevation Myocardial Infarction

Abstract: High NGAL levels may be associated with poor prognosis after PCI in patients with STEMI. However, further studies with larger numbers of patients and longer follow-up are required to evaluate the usefulness of plasma NGAL level for predicting prognosis of STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…The median (interquartile range) time from ICU arrival to collection of the first samples was 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) hours. At least 3 months of follow-up data were available for 639 (92.3%) patients, and full 9-month outcome was known for 552 (79.8% of the initial cohort) patients, with 217 (39.3% of those with complete follow-up) patients meeting the primary end point of death or dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…The median (interquartile range) time from ICU arrival to collection of the first samples was 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) hours. At least 3 months of follow-up data were available for 639 (92.3%) patients, and full 9-month outcome was known for 552 (79.8% of the initial cohort) patients, with 217 (39.3% of those with complete follow-up) patients meeting the primary end point of death or dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies which use NGAL for risk stratification in patients with unstable angina (UA) [9] and acute myocardial infarction (AMI) [10,11], but its role in patients with stable angina was not established. Furthermore, most of the studies concentrate on short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that high plasma NGAL concentration measured 30 minutes before PCI independently predicts all-cause mortality and major adverse cardiovascular events (MACE) after STEMI on a 2-year follow-up. In another recent study investigators demonstrated that high NGAL concentration is a predictor of in-hospital and 1-year mortality and MACE in patients with STEMI [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that NGAL is a strong marker of outcome in patients with acute myocardial infarction and HF. 31,32 We have also shown this in 584 patients with ST-segmentelevation myocardial infarction.…”
mentioning
confidence: 93%